Perfusion-weighted imaging and dynamic 4D angiograms for the estimation of collateral blood flow in lacunar infarction - Förster, Alex; Mürle, Bettina; Böhme, Johannes; Al-Zghloul, Mansour; Kerl, Hans Ulrich; Wenz, Holger; Groden, Christoph (Journal of cerebral blood flow & metabolism, 2016)
Although lacunar infarction accounts for approximately 25% of ischemic strokes, collateral blood flow through anastomoses is not well evaluated in lacunar infarction. In 111 lacunar infarction patients, we analyzed diffusion-weighted images, perfusion-weighted images, and blood flow on dynamic four-dimensional angiograms generated by use of Signal Processing In NMR-Software. Blood flow was classified as absent (type 1), from periphery to center (type 2), from center to periphery (type 3), and combination of type 2 and 3 (type 4). On diffusion-weighted images, lacunar infarction was found in the basal ganglia (11.7%), internal capsule (24.3%), corona radiata (30.6%), thalamus (24.3%), and brainstem (9.0%). In 58 (52.2%) patients, perfusion-weighted image showed a circumscribed hypoperfusion, in one (0.9%) a circumscribed hyperperfusion, whereas the remainder was normal. In 36 (62.1%) patients, a larger perfusion deficit (>7 mm) was observed. In these, blood flow was classified type 1 in four (11.1%), 2 in 17 (47.2%), 3 in 9 (25.0%), and 4 in six (16.7%) patients. Patients with lacunar infarction in the posterior circulation more often demonstrated blood flow type 2 and less often type 3 (p = 0.01). Detailed examination and graduation of blood flow in lacunar infarction by use of dynamic four-dimensional angiograms is feasible and may serve for a better characterization of this stroke subtype.